1998
DOI: 10.1128/jb.180.14.3556-3562.1998
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Carboxy-Terminal Half of Pseudomonas aeruginosa Major Outer Membrane Protein OprF in Cell Shape, Growth in Low-Osmolarity Medium, and Peptidoglycan Association

Abstract: OprF, the major outer membrane protein of Pseudomonas aeruginosa, is multifunctional in that it can act as a nonspecific porin, plays a role in the maintenance of cell shape, and is required for growth in a low-osmolarity environment. The latter two structural roles of OprF, and OprF’s association with the peptidoglycan, have been proposed to be localized in the carboxy terminus of the protein, based on this region’s similarity to members of the OmpA family of proteins. To determine if this is correct, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…The similar ion channel activity of the three N-terminal domains observed in the present study suggests that the pores of OprF 175 and OprF 177 are very likely constituted of eight L-strands as OmpA 171 . This would con¢rm the previous structural predictions made for the N-terminal domain of OprF [11,13,20]. Thus, ion channel activity data and structural models would suggest similar function for the amino-terminal ends of OprFs and OmpA.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The similar ion channel activity of the three N-terminal domains observed in the present study suggests that the pores of OprF 175 and OprF 177 are very likely constituted of eight L-strands as OmpA 171 . This would con¢rm the previous structural predictions made for the N-terminal domain of OprF [11,13,20]. Thus, ion channel activity data and structural models would suggest similar function for the amino-terminal ends of OprFs and OmpA.…”
Section: Resultssupporting
confidence: 84%
“…Without crystallographic data to date, the functional tertiary structure of OprF is not well established. Nikaido's group agrees with a periplasmic C-terminal part [12], whilst other authors hypothesise that OprF is constituted of 16 L-strands, suggesting that the structure of the C-terminal part is not globular [11,13]. Nevertheless, there is no consensus to propose the number of L-strands necessary for building the ion channel in native OprF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the translocation of the C-terminal domain between the periplasm and the surface can modulate the pore size (Nikaido, 2003;Tamber and Hancock, 2004). Putative selection factors could be related to one or several known functions of the protein: adhesion (de Mot et al, 1994), nutrient uptake (Orange, 1994) or resistance to a variation of osmotic pressure (Rawling et al, 1998). In P. aeruginosa, it has even been reported that the binding of human interferon-γ to OprF results in the expression of the PA-I lectin, a quorum-sensing-dependent virulence determinant (Wu et al, 2005).…”
Section: Fieldmentioning
confidence: 99%
“…Although OprF has been found also in Azotobacter vinelandii , this species should certainly be classified in Pseudomonas genus (Rediers et al ., 2004). OprF is a pleiotropic protein that plays a role as porin (Orange, 1994), membrane structural protein (Rawling et al ., 1998) and root adhesive (de Mot et al ., 1992). This protein has been studied extensively due to its utility as a vaccine component, its role in antimicrobial drug resistance and its porin function (Orange, 1994;De et al ., 1995;Rawling et al ., 1995;Jaouen et al ., 2004;Worgall et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%